Biosphere Reserve for All: Potentials for Involving Underrepresented Age Groups in the Development of a Biosphere Reserve through Intergenerational Practice - Mitrofanenko, Tamara (Environ Manage, 2018)
Stakeholder participation is of high importance in UNESCO biosphere reserves as model regions for sustainable development; however, certain groups remain underrepresented. The paper proposes Intergenerational Practice (IP) as a means of involving youth and elderly women and explores its options and barriers, using the example of the Salzburger Lungau and Kärntner Nockberge Biosphere Reserve in Austria. Case study analysis is used involving mixed methods. The results reveal obstacles and motivations to participating in biosphere reserve implementation and intergenerational activities for the youth and the elderly women and imply that much potential for IP exists in the biosphere reserve region. The authors propose suitable solutions from the intergenerational field to overcome identified participation obstacles and suggest benefits of incorporating IP as a management tool into biosphere reserve activities. Suggestions for future research include evaluating applications of IP in the context of protected areas, testing of methods used in other contexts, and contribution to theory development.